In the Pursuit of Synchrony: Northward Shifts in Western Spruce Budworm Outbreaks in a Warming Environment - Tai, Amberly R.; Carroll, Allan L. (Frontiers in Forests and Global Change, 2022)
Outbreaks of western spruce budworm (Choristoneura freemani Freeman) in Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) forests of western Canada have shifted northward in recent decades. Using forest health survey data collected during the previous century (1909 to 2011) to assess the pattern of range shifts, we found that outbreaks have rapidly shifted to higher latitudes and elevations while gradually retracting from the southern and western portions of its range. Given that the survival of western spruce budworm is affected by access to developing buds, we tested the prediction that this shift was associated with climate change-induced alterations in synchrony between budworm larval emergence and Douglas-fir bud development. We simulated the dates of larval emergence and host budburst annually from 1901 to 2011 using existing phenology models and long-term weather data. Over the last century, the timing of larval emergence in relation to budburst has converged towards optimal synchrony at higher latitudes and elevations, while diverging at lower latitudes and elevations. Shifting synchrony arises from differential responses to temperature by the insect and its host tree; both are reliant upon degree day accumulation, but Douglas-fir bud development is putatively dependent upon an additional photoperiodic threshold. Thus, the potential for warming to cause directional shifts in phenological matching between early season folivores and their host trees may be contingent upon the degree to which each depends on different components of their environments for their development.